Tuberculosis in HIV/AIDS patients: a Malaysian experience - Nissapatorn, V.; Kuppusamy, I.; Sim, B.L.H.; Quek, K.F.; Khairul Anuar, A. (Seameo Regional Tropical Medicine & Public Health, 2005)
This retrospective study was conducted at the National Tuberculosis Center (NTBC) where 252 HIV-positive patients coexisting with tuberculosis (TB/HIV) were examined. We found that patients with pulmonary (PTB) and extrapulmonary tuberculosis (EPT) had similar mean age. A higher sex ratio between male to female (10.7:1) was observed in patients with PTB. The other characteristics of patients with pulmonary and extrapulmonary tuberculosis were not statistically different from each other. Cough (88) and hemoptysis were the most common presenting symptoms, significantly related to patients with PTB. Lymphadenopathy (33.5) was the most common sign in patients with EPT. The majority of patients with pulmonary and extrapulmonary tuberculosis had CD4 cell counts of less than 200 cells/mm3 (range 0-1,179 with a median of 57 cells/mm3). Lung (89) and miliary (55.6) forms were the most frequent disease locations in patients with PTB and EPT, respectively. A higher percentage of patients with PTB (42) were treated successfully with short-course (6 months) therapy, whereas in patients with EPT (43) needed a longer period (9 months) for successful treatment. Of the patients who defaulted treatment, a higher proportion (87) had PTB. No MDR-TB or relapse cases were found in this study.